Legal challenges of solitary and joint commitments of the European Union member states toward the refugees and immigrants / desafios legais dos compromissos solitários e conjuntos dos Estados-membros da União Europeia em relação aos refugiados e.... - Kadkhodaei, Abbas; Rostami, Soraya (Revista de Direito da Cidade, 2018)
DOI: 10.12957/rdc.2018.31822 Abstract European immigration laws are more subjected to domestic law than the European system. Rules like Dublin Regulation lost their efficiency in the Refugees crisis. According to Direct Effect Rule, If the EU legislate immigration rules, member states are obliged to comply with it. Legally, the EU’s outsourcing policy (transference the immigrants to countries of origin or third parties due to readmission contract) and providing the needed manpower by the blue card system are against the humanitarian rules and conventions on refugees. In this theoretical paper; we’ve used describing-analytical method and with the attributive- bibliothecal technique attempted to answer the question of the impacts of the refugees crisis on legal commitments of the EU’s member states. So, through legal differences between concepts of immigrant, refugee and asylum seeker we tried to verify the theory “because of the unevenness in legal commitments of the European states and the lack of dynamism in European approaches, the existing laws are ineffective and not competence of handling this situation”. In order to conformity to international conventions, the EU must classify the refugees, based on international criterions with the priority of Syrian refugees, and take an appropriate approach, also pass joint rules about this subject, and try to bold the role of European laws in managing the immigration field and create more effective legal system too. That is necessary from the humanitarian point of view and also for the maintenance of European institutions effectiveness and existence. Keywords: The European Union; The Refugee Crisis; The European Laws; The Refugee Convention; Reassignment Resumo As leis europeias de imigração estão mais sujeitas à legislação nacional do que o sistema europeu. Regras como Dublin Regulation perderam sua eficiência na crise dos refugiados. De acordo com a Regra de Efeito Direto, se a UE legislar as regras de imigração, os Estados membros são obrigados a cumpri-las. Legalmente, a política de terceirização da UE (transferência de imigrantes para países de origem ou de terceiros devido a contrato de readmissão) e fornecer a mão-de-obra necessária pelo sistema de cartão azul são contra as regras e convenções humanitárias sobre refugiados. Neste artigo teórico, usamos o método analítico descritivo e com a técnica bibliográfica atributiva tentou-se responder a questão dos impactos da crise dos refugiados sobre os compromissos legais dos Estados membros da UE. Assim, através de diferenças legais entre os conceitos de imigrante, refugiado e requerente de asilo, tentamos verificar a teoria "por causa da desigualdade nos compromissos legais dos estados europeus e da falta de dinamismo nas abordagens europeias, as leis existentes são ineficazes e não a competência de lidar com esta situação". Para a conformidade com as convenções internacionais, a UE deve classificar os refugiados, com base em critérios internacionais com a prioridade dos refugiados sírios, e adotar uma abordagem apropriada, também aprovar regras comuns sobre este assunto e tentar enfatizar o papel das leis europeias em gerenciar o campo da imigração e criar um sistema jurídico mais efetivo também. Isso é necessário do ponto de vista humanitário e também para a manutenção da eficácia e da existência das instituições europeias. Palavras-chave: União Européia, Crise dos Refugiados, Leis Européias, Convenção dos Refugiados, Reatribuição